The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fbioe.2022.1057429
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid ameliorates intervertebral disc degeneration via promoting mitophagy activation

Abstract: Activation of mitophagy was considered to be a potential therapeutic strategy for intervertebral disc degeneration (IDD). There was evidence suggesting that hyaluronic acid (HA) can protect mitochondria from oxidative stress in chondrocytes, but its protective effects and mechanism in nucleus pulposus cells (NPCs) remain unclear. This study aimed to confirm the effect of HA promoting mitophagy and protecting mitochondria function in NPCs, and explore its underlying mechanism. NPCs were treated with high molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Firstly, Alini et al demonstrated that a matrix of type I collagen and HA supplied stimulated the production of proteoglycans in both NPCs and AFCs. When HA is administered to cultured NPCs derived from human degenerating discs it stimulates mitophagy which has downstream protective effects against apoptosis and degradation of the ECM [99]. Similar ECM-protective effects of HA were demonstrated in a separate study examining the application of a HA hydrogel with fibroblast growth factor in both human and bovine NPCs [100].…”
Section: Adjunct Materials -Hyaluronic Acidmentioning
confidence: 63%
“…Firstly, Alini et al demonstrated that a matrix of type I collagen and HA supplied stimulated the production of proteoglycans in both NPCs and AFCs. When HA is administered to cultured NPCs derived from human degenerating discs it stimulates mitophagy which has downstream protective effects against apoptosis and degradation of the ECM [99]. Similar ECM-protective effects of HA were demonstrated in a separate study examining the application of a HA hydrogel with fibroblast growth factor in both human and bovine NPCs [100].…”
Section: Adjunct Materials -Hyaluronic Acidmentioning
confidence: 63%
“…Firstly, Alini et al [ 100 ] demonstrated that a matrix of type I collagen and supplied HA stimulated the production of proteoglycans in both NPCs and AFCs. When HA is administered to cultured NPCs derived from human degenerating discs it stimulates mitophagy which has downstream protective effects against apoptosis and degradation of the ECM [ 101 ]. Similar ECM-protective effects of HA were demonstrated in a separate study examining the application of a HA hydrogel with fibroblast growth factor in both human and bovine NPCs [ 102 ].…”
Section: Orthobiologic Solutionsmentioning
confidence: 99%